Health-Related Quality of Life and Distress of Parents of Children With Avoidant Restrictive Food Intake Disorder. Issue 1 (July 2021) - Krom, Hilde; van Oers, Hedy A.; van der Sluijs Veer, Liesbeth; van Zundert, Suzanne M.C.; Otten, Marie-Anne G.M.; Haverman, Lotte; Benninga, Marc A.; Kindermann, Angelika
ABSTRACT: Objectives: Health-related quality of life (HRQOL) of children with avoidant restrictive food intake disorder (ARFID) is impaired. Aim: To measure HRQOL and distress of parents of children with ARFID. Methods: Cross-sectional cohort study. Parents of children with ARFID, visiting our multidisciplinary feeding team, completed questionnaires on the online Quality of Life in Clinical Practice portal; the Questionnaire for Adult's Health Related Quality of Life to assess parental HRQOL and the Distress Thermometer for Parents. Reference groups of parents of healthy (HC) and chronically ill children (CIC) were used. Results: Eighty-five mothers and 62 fathers of 89 children with ARFID (58% female, median age 1.9 years) were included (response rate 68%). No differences were found regarding HRQOL in 11 of 12 domains between parents of children with ARFID and HC. Mothers of children with ARFID reported significantly higher HRQOL regarding pain and fathers a significantly lower HRQOL on depressive emotions compared to HC. No differences were found in overall and clinical distress scores between parents of children with ARFID and HC/CIC. Mothers of children with ARFID had significantly higher distress scores regarding cognitive problems compared to HC and parenting problems in children <2 years compared to HC/CIC. Significantly higher distress scores on parenting problems in children <2 years were found in fathers of children with ARFID compared to HC/CIC. Conclusion: Most HRQOL and distress scores of parents of children with ARFID were comparable to reference groups. Since parents of children with ARFID perceive a lack of understanding and support from the environment, professionals should suggest peer support through patient's organizations. Furthermore, it is important to offer professional support since parents indicated that they would like to talk to a professional about their situation. Abstract : Supplemental Digital Content is available in the text